The Role of Inter- and Intraindustry Trade in Technology Diffusion - Hakura, Dalia (IMF Working Papers; Working Paper ;, 1999)
Research shows that international trade is an important channel for the transfer of technology. Building on this evidence, this paper examines the effects of inter- and intraindustry trade on technology transfer. The paper develops and tests the hypothesis that intraindustry trade stimulates more technology transfer than interindustry trade because countries are likely to absorb foreign technologies more easily when their imports are from the same sectors as their production and export sectors. The results of empirical tests for 87 countries during 1970-93 support this hypothesis.